Implementation of Kashmir as an independent state in South Asia - Muhammad Haziq Khan; Hassan Khan; Danish Hanif (Indonesian Journal of Social Sciences, 2022)
The study investigates the conflict between India and Pakistan over Kashmir as a manifestation of a disagreement between the two countries and emphasizes the factors that are required for the state to act independently, including international law perspective, economic history, natural resource production, geography, and culture. According to the findings of the study, India and Pakistan have rejected the first two options of formal partition and autonomy, but the third option, an independent state, will remain the most viable option for the foreseeable future because neither India nor Pakistan can rule the entire region of Kashmir. As a result, the emergence of an independent state in Asia is considered a legitimate, negotiated solution to the Kashmir dispute. It is asserted here that as long as both India and Pakistan maintain their historically defensive positions, there is little hope for long-term peace in Kashmir. The study further contends that Kashmir's independence is the only way to ensure a long-term settlement to the Kashmir dispute as well as regional peace in Southeast Asia.